The Disposal of Indonesian Crew Members of Long Xing 629 Vessel in the Pacific Ocean - Juana Clarentine Emmanuela Greevince De Lucas; Axel Adam Mahendra; Audrey Nethania Wibowo; Galvin Hapsari Putri; Randhi Satria (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2023)
Modern slavery in fishing industries is still a problem in maritime-based countries such as Indonesia. One of the recent cases is the disposal of Indonesian crew members in the Pacific Ocean by China fishing vessel Long Xing 629 in 2020. As a result, Indonesian crew members once again become modern slavery victims in the fishing industry. This article analyzes how Indonesian crew members became the victims of modern slavery in Long Xing 629. This paper will use descriptive qualitative research within the data collected from books, journals, articles, and news. In addition, the Eleven Categories of Forced Labor by ILO and Modern Slavery Theory by Andrew Crane will use to help analyze the case. The research shows that Indonesian crew members of Long Xing 629 become the victims of modern slavery due to their socio-economic conditions, such as poverty and low education. This condition is also supported by weak state regulation, such as weak government protection and lack of government attention, which conditions tend to lure and trap them in modern slavery. This paper believes that it will contribute to the modern slavery study in the fishing industry research field to help reduce and resolve a similar case in the future. Keywords: Indonesian ship crew, Long Xing 629, modern slavery